2009
DOI: 10.1111/j.1365-2923.2008.03277.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical ethics contributes to clinical management: teaching medical students to engage patients as moral agents

Abstract: OBJECTIVES In order to teach medical students to engage more fully with patients, we offer ethics education as a tool to assist in the management of patient health issues. METHODS We propose that many dilemmas in clinical medicine would benefit by having the doctor embark on an iterative reasoning process with the patient. Such a process acknowledges and engages the patient as a moral agent. We recommend employing Kant’s ethic of respect and a more inclusive definition of patient autonomy drawn from philosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…They have also have established innovative tools to allow the two parties’ processes to conform to one another’s expectations, including studies on the risk/benefit analysis for the use of Tysabri 15. An impressive literature has accrued concerning the medical decision-making process utilizing qualitative as well as quantitative data 21,29,30,34…”
Section: Working Out the Details Of Managing Disagreement On Riskmentioning
confidence: 99%
“…They have also have established innovative tools to allow the two parties’ processes to conform to one another’s expectations, including studies on the risk/benefit analysis for the use of Tysabri 15. An impressive literature has accrued concerning the medical decision-making process utilizing qualitative as well as quantitative data 21,29,30,34…”
Section: Working Out the Details Of Managing Disagreement On Riskmentioning
confidence: 99%
“…4,5 It has also been demonstrated that ability in ethical reasoning is a predictor of clinical performance 6 and facilitates clinical decision making. 7 Ethical reasoning can be defined as a problem solving process which requires a knowledge of ethical theory; a knowledge of the perspectives and values of those involved in the ethical scenario; a knowledge of self as practitioner; and an ability to articulate these different types of knowledge and associated values in the reasoning process. 8 Ethical reasoning is used interchangeably with the term moral judgement in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura [10][11][12][13][14][15][16] atesta tal afirmação, demonstrando que, nas escolas médicas, a construção da postura ética e o pensamento crítico e reflexivo se desenvolvem a partir de disciplinas e condutas que se aprendem nas salas de aula, nos laboratórios e, principalmente, observando os professores em ação na práti-ca cotidiana. Ao mesmo tempo em que afirmam que os alunos, pela observação dos mestres, "modelam" comportamentos e, assim, de certa forma, constroem uma identidade médica, tais estudos contrariam a suposição de que os alunos, por serem adultos com personalidades já formadas, não modificariam valores e atitudes mediante aprendizado na escola médica.…”
Section: Introductionunclassified